2020
DOI: 10.3346/jkms.2020.35.e67
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Cannula Oxygen Therapy Can Be Effective for Patients in Acute Hypoxemic Respiratory Failure with Hypercapnia: a Retrospective, Propensity Score-Matched Cohort Study

Abstract: Background: Usually, high-flow nasal cannula (HFNC) therapy is indicated for de novo acute hypoxemic respiratory failure (AHRF). Although only a few researches have examined the effectiveness of HFNC therapy for respiratory failure with hypercapnia, this therapy is often performed under such conditions for various reasons. We investigated the effectiveness of HFNC therapy for AHRF patients with hypercapnia compared to those without hypercapnia. Methods: All consecutive patients receiving HFNC therapy between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
4
0
3
Order By: Relevance
“…Post-hoc analysis also showed that HFNC therapy seemed to be better than non-invasive ventilation or standard oxygenation for immunocompromised patients [4]. However, although beneficial effects have been reported for patients with various medical conditions [23][24][25][26][27], HFNC therapy for sepsis patients at risk of hemodynamic instability has not been sufficiently evaluated. Hence, our study is clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-hoc analysis also showed that HFNC therapy seemed to be better than non-invasive ventilation or standard oxygenation for immunocompromised patients [4]. However, although beneficial effects have been reported for patients with various medical conditions [23][24][25][26][27], HFNC therapy for sepsis patients at risk of hemodynamic instability has not been sufficiently evaluated. Hence, our study is clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who undergo noninvasive therapy for AHRF, the respiratory rate and oxygenation level are important predictors of respiratory failure and the need for intubation [9,27,33,39]. Tracking dynamic changes in these parameters during HFNC therapy is important [9,39].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, HFOT is generally explored for patients with acute respiratory distress and supportive results have been suggested ( 19 ). In an animal model experiment comparing HFOT and CPAP, a significant decrement in CO 2 levels with HFOT was observed, and HFOT was suggested as an alternative for CPAP ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Utilizaron caudales no superiores a 50 L/min y FiO 2 <0,5 y, al compararlo con SO, observaron una reducción en la concentración de CO 2 . Finalmente, Bae et al 64 evaluaron la eficacia de la CNAF en comparación con pacientes que solo tenían IRA y observaron que la mortalidad hospitalaria y en la UCI sin ajustar era menor en los pacientes con CNAF. Al ajustar estos datos no se encontraron diferencias significativas.…”
Section: Cnaf En Pacientes Críticosunclassified